1990
DOI: 10.1037/0012-1649.26.4.589
|View full text |Cite
|
Sign up to set email alerts
|

Velocity thresholds in human infants: Implications for the perception of motion.

Abstract: Infants' perception of the direction and speed of motion could be mediated by several underlying mechanisms, including sensitivity to temporal variations in luminance, the relative position of pattern elements, or time-locked spatial displacements. Velocity thresholds were estimated in 6-and 12-week-old infants who viewed a set of moving stripes surrounded by sets of stationary stripes. The forced-choice preferential looking technique was used to collect data from infants who were presented with high-contrast … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
38
1
1

Year Published

1992
1992
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(46 citation statements)
references
References 43 publications
6
38
1
1
Order By: Relevance
“…In the case of an autonomous change (excluding cyclic movements such as those associated with a bouncing ball), Premack suggests that infants perceive intentionality and show preference toward these objects. While adults can identify the nature of a self-propelled object and associate intentionality to it, for infants what matters is not the object but the type of movements it generates (Sekuler 1975) and its velocity (Aslin and Shea 1990;Dannemiller and Freeland 1989). A child is also able to attribute self-propelled capabilities once having seen the robot intentionally moving, and this association will continue even when the robot has stopped (Premack 1990).…”
Section: Mobile Robots and Autismmentioning
confidence: 99%
“…In the case of an autonomous change (excluding cyclic movements such as those associated with a bouncing ball), Premack suggests that infants perceive intentionality and show preference toward these objects. While adults can identify the nature of a self-propelled object and associate intentionality to it, for infants what matters is not the object but the type of movements it generates (Sekuler 1975) and its velocity (Aslin and Shea 1990;Dannemiller and Freeland 1989). A child is also able to attribute self-propelled capabilities once having seen the robot intentionally moving, and this association will continue even when the robot has stopped (Premack 1990).…”
Section: Mobile Robots and Autismmentioning
confidence: 99%
“…Consistent with our findings, Banton and Bertenthal (1996) found better performance for faster speeds with a uniform motion display and no change in overall sensitivity over an age range comparable to that studied by Wattam-Bell. Also, several other studies have reported substantial improvements in sensitivity to slow speeds over the range 2-6 months (Aslin & Shea, 1990;Finlay et al, 1991, Roessler & Dannemiller, 1997.…”
Section: Determinants Of Sensitivity To Speedmentioning
confidence: 99%
“…Behavioral estimates of the lower velocity limit eliciting motion responses in infants cover a broad range (from 1.2 deg/sec to 22.3 deg/sec), depending on the age range tested -6-8 weeks: 3 deg/sec (Banton & Bertenthal, 1996;Kaufmann, Stucki, & Kaufmann-Hayoz, 1985) to 9 deg/sec (Aslin & Shea, 1990); 12-14 weeks: 2-3 deg/sec (Bertenthal & Bradbury, 1992;Dannemiller & Freedland, 1993) to 22.3 deg/sec (Dobkins & Teller, 1996); 20 weeks: 1.2 deg/sec (Bertenthal & Bradbury, 1992) to 2 deg/sec (Dannemiller & Freedland, 1989).…”
Section: Velocity Limits For Motion Processing In Infantsmentioning
confidence: 99%